Relic - Preston, Douglas J.; Child, Lee (Preston, Douglas J. Pendergast novel., 2024)
"Just days before a massive exhibition opens at the popular New York Museum of Natural History, visitors are being savagely murdered in the museum's dark hallways and secret rooms. Autopsies indicate that the killer cannot be human... But the museum's directors plan to go ahead with a big bash to celebrate the new exhibition, in spite of the murders. Museum researcher Margo Green must find out who--or what--is doing the killing. But can she do it in time to stop the massacre?" -- Amazon.com